Penerapan Metode Topsis Dalam Pemilihan Jasa Ekspedisi - Iin Mutmainah; Yunita Yunita (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2021)
Many factors influence the selection of expedition services, such as the length of delivery, the price offered to the services provided. At first the company chose the expedition service partner based solely on customs, but often there were obstacles such as unsatisfactory service, less neat packing of goods, high prices and so forth. The impact is the customer's disappointment with the service we provide.In selecting the best expedition services, a mechanism is needed to deliver the goods that are truly feasible. One of them can be done by using a decision support system with the topsis method. Where the TOPSIS method has a simple and easy-to-understand concept and has the ability to measure the relative performance of decision alternatives in a simple mathematical form. The criteria used in this study include price, service, delivery time, range, type of fleet and company experience, while alternative options for expedition services are Ezra Cargo, Sentral Cargo, Dakota Cargo, Indah Logistik Cargo, Run Logistics, Trans Java Sumatra. The results of calculations using the Topsis method can be said that, the selection of the best expeditionary services is Central Cargo with first place with a value of 0,8887, then followed by Indah Logistik Cargo with second place with a value of 0,5866, and third place is Ezra Cargo with a value of 0,5444. Thus, Central Cargo is the best solution in the selection of expedition services at PT. Tachimita Hoka Utama.